E1. Risk of chronic hypertension in women with a history of hypertensive disorders of pregnancy – a nationwide cohort study. (12th August 2016) - Behrens, I.; Basit, S.; Melbye, M.; Lykke, J. A.; Wohlfahrt, J.; Bundgaard, H.; Thilaganathan, B.; Boyd, H. A.
Abstract: Background : Women with a history of hypertensive disorders of pregnancy (HDP) are known to have an increased risk of hypertension years after their pregnancy. However, how soon after an affected pregnancy the risk of hypertension increases and how/whether this risk evolves over time, is unclear. Method : Using national health register data, we identified all women giving birth in Denmark from 1978 to 2011. Cox regression analysis was used to compare the rates of incident post-pregnancy hypertension requiring treatment with medication after pregnancy in women with and without a history of HDP, by the number of years since pregnancy. Findings : In the first 3 years after a woman's latest pregnancy, rates of chronic hypertension were 4- to 9-fold higher in women with an HDP in that pregnancy than in women with a normotensive pregnancy. The difference in rates between the two groups declined progressively with time, but even after ≥20 years, rates of chronic hypertension were twice as high among women with an HDP in their latest pregnancy. Gestational hypertension was associated with significantly higher rates of later hypertension than preeclampsia, while moderate and severe preeclampsia were associated with similar increases in risk of later hypertension. Women with HDP-affected pregnancies in their 20s, 30s and 40s, respectively had 10-year cumulative incidences of chronic hypertension between 10% and 30%, whereas for women with normotensive pregnancies in their 20s, 30s and 40s, the corresponding cumulative incidences fell between 4% and 12% (for all three age groups, the cumulative incidences for the HDP and non-HDP groups were statistically significantly different). Interpretation : The increased risk of chronic hypertension associated with a previous HDP is already present soon after delivery, and is substantial in all age groups. Women with an HDP affected pregnancy in their 20s had the same post-pregnancy 10-year cumulative risk of chronic hypertension as women with normotensive pregnancies who were 20 years older. These findings suggest that blood pressure monitoring in women with a history of HDP should be initiated soon after the affected pregnancy.